2018
DOI: 10.1167/iovs.18-23878
|View full text |Cite
|
Sign up to set email alerts
|

Retest Reliability of Mesopic and Dark-Adapted Microperimetry in Patients With Intermediate Age-Related Macular Degeneration and Age-Matched Controls

Abstract: FG, Finger RP. Retest reliability of mesopic and dark-adapted microperimetry in patients with intermediate age-related macular degeneration and age-matched controls. Invest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Both, mesopic and darkadapted microperimetry revealed reduced retinal sensitivity in iAMD patients compared to controls. These results are in accordance with findings from previous studies, which found mesopic microperimetry to be a good functional test in iAMD [20,48,49,12,14,37,8,50,5]. Contrary to our findings Nebbioso and colleagues reported a reduction in scotopic sensitivity but not mesopic sensitivity in patients with hard drusen [51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Both, mesopic and darkadapted microperimetry revealed reduced retinal sensitivity in iAMD patients compared to controls. These results are in accordance with findings from previous studies, which found mesopic microperimetry to be a good functional test in iAMD [20,48,49,12,14,37,8,50,5]. Contrary to our findings Nebbioso and colleagues reported a reduction in scotopic sensitivity but not mesopic sensitivity in patients with hard drusen [51].…”
Section: Discussionsupporting
confidence: 93%
“…In our sample of more advanced AMD mesopic microperimetry seemed to be a better test compared to dark-adapted microperimetry. This may be attributable to the higher variability of dark-adapted microperimetry compared to mesopic microperimetry [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 As previously described, a customized stimulus grid was used that consisted of 33 points located at 0°, 1°, 3°, 5°, and 7°from fixation. 25 First, mesopic testing was performed. Patients were not dark-adapted, but the room light was switched off just before the examination.…”
Section: Functional Testingmentioning
confidence: 99%
“…Microperimetry is becoming increasingly popular for the assessment of the differential light sensitivity in macular disease. [1][2][3][4][5][6][7][8] The principal advantage of microperimetry compared with standard automated perimetry (SAP) is the provision of fundus tracking that adjusts the position of each stimulus location to account for fixation instability and/or for eccentric fixation, both of which are common in late stage macular disease. Additionally, the measured sensitiv-ity at any given stimulus location is superimposed, in real time, upon the fundus image thereby providing an indication of the topographical relationship between visual function and fundal abnormality.…”
Section: Introductionmentioning
confidence: 99%